2020
DOI: 10.1111/fare.12474
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents' and Parents' Perspectives: A Gaming Disorder Intervention in Singapore

Abstract: ObjectiveThis study aimed to understand useful components and mechanisms in treating adolescent gaming disorder.BackgroundAlthough video gaming has become a pervasive part of adolescents' daily life that can lead to educational, physical, psychological, and social problems, there is ongoing debate as to whether this is an addiction, and there is little evidence about treatment effectiveness.MethodThis process research used a case study design and conducted individual semistructured interviews with 10 male adol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 55 publications
2
19
0
Order By: Relevance
“…Putting the results into cultural context and considering the traditional Chinese collective core family values, family involvement in the treatment process addresses the entire family as a unit [ 8 , 29 ]. This fits with the findings from a Singapore study that active parental participation in intervention programs is an effective, culturally relevant solution in the Asian context [ 28 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Putting the results into cultural context and considering the traditional Chinese collective core family values, family involvement in the treatment process addresses the entire family as a unit [ 8 , 29 ]. This fits with the findings from a Singapore study that active parental participation in intervention programs is an effective, culturally relevant solution in the Asian context [ 28 ].…”
Section: Discussionsupporting
confidence: 89%
“…This finding coincides with results from previous research, such as Liu et al [ 18 ] and Zhong et al [ 16 ], that found that strengthened family cohesion and dynamics have profound effects on ameliorating IA behaviors. In accordance with recently published qualitative research on parents’ perspectives in gaming disorder interventions, counselors who put adequate emphasis on addressing family tensions and mediating turbulent parent–child relationships manage to expedite the treatment process [ 28 ]. Therefore, it is suggested that family involvement in IA treatment should encompass enhancing communication proficiency and fostering positive family interactions and functionality.…”
Section: Discussionmentioning
confidence: 96%
“…Given the early state of research on this complex and novel disorder, individual experiences of patients and experienced practitioners are of high relevance for the development and the evaluation of treatment programs. To the best of our knowledge, until today only one qualitative study has been published that investigated adolescents' perspectives on useful components and mechanisms in the treatment of problematic gaming behavior by semi-structured interviews [32]. The sample of Sim et al consisted of 10 boys from 13 to 18 years and 11 parents who had participated in the Cyber Wellness Enrichment Program (CWEP) within two years before the interview [32].…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, until today only one qualitative study has been published that investigated adolescents' perspectives on useful components and mechanisms in the treatment of problematic gaming behavior by semi-structured interviews [32]. The sample of Sim et al consisted of 10 boys from 13 to 18 years and 11 parents who had participated in the Cyber Wellness Enrichment Program (CWEP) within two years before the interview [32]. The authors do not give information on comorbidities, diagnostic criteria, and the severity of the problematic behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Both were formalised as disorders in 2019. Consequently, literature about the research and treatment of IGD and GD is fairly recent, and although some case studies do exist [8][9][10][11][12] they are few in number, tend to provide little detailed information about each case and typically use the cases of older teenagers 14 to 19 years old [8,10,13]. The objective of the current case series study is to evaluate the symptom profile, assessment process, treatment and outcomes for a case series of young adolescents aged 11-13 years who had presented to a treatment clinic seeking help for IGD/GD.…”
Section: Introductionmentioning
confidence: 99%